Antiproliferative activity and apoptosis-inducing mechanism of Amaryllidaceae alkaloid montanine on A549 and MOLT-4 human cancer cells - Koutova, Darja; Maafi, Negar; Muthna, Darina; Kralovec, Karel; Kroustkova, Jana; Pidany, Filip; Timbilla, Abdul Aziz; Cermakova, Eva; Cahlikova, Lucie; Rezacova, Martina; Havelek, Radim (Biomedicine & pharmacotherapy, 2023)
The isoquinoline alkaloids found in Amaryllidaceae are attracting attention due to attributes that can be harnessed for the development of new drugs. The possible molecular mechanisms by which montanine exerts its inhibitory effects against cancer cells have not been documented. In the present study, montanine, manthine and a series of 15 semisynthetic montanine analogues originating from the parent alkaloid montanine were screened at a single test dose of 10 μM to explore their cytotoxic activities against a panel of eight cancer cell lines and one non-cancer cell line. Among montanine and its analogues, montanine and its derivatives 12 and 14 showed the highest cytostatic activity in the initial single-dose screening. However, the native montanine exhibited the greatest antiproliferative activity against cancer cells, with a lower mean IC50 value of 1.39 μM, compared to the displayed mean IC50 values of 2.08 μM for 12 and 3.57 μM for 14. Montanine exhibited the most potent antiproliferative activity with IC50 values of 1.04 μM and 1.09 μM against Jurkat and A549 cell lines, respectively. We also evaluated montanine's cytotoxicity and cell death mechanisms. Our results revealed that montanine triggered apoptosis of MOLT-4 cells via caspase activation, mitochondrial depolarisation and Annexin V/PI double staining. The Western blot results of MOLT-4 cells showed that the protein levels of phosphorylated Chk1 Ser345 were upregulated with increased montanine concentrations. Our findings provide new insights into the mechanisms underlying the cytostatic, cytotoxic and pro-apoptotic activities of montanine alkaloids in lung adenocarcinoma A549 and leukemic MOLT-4 cancer cell types.
Keywords: cytostatické látky; Apoptosis; isochinoliny; Amaryllidaceae Alkaloids; Lung Neoplasms; nádory plic; Cytostatic Agents; alkaloidy; alkaloidy amarylkovitých; Amaryllidaceae; Antineoplastic Agents; protinádorové látky; Alkaloids; Humans; lidé; apoptóza; Isoquinolines